2006
DOI: 10.1080/09638280500476188
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality and scalability of the Motor Assessment Scale (MAS)

Abstract: We conclude that the scalability of the different items is not optimal. For some items, the top and/or bottom levels are overrepresented and for other items the middle levels tend to cluster. There seems to be a single construct except for one of the items. The instrument also showed the same meaning for the different subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…As reported by many researchers, the MAS has significant floor and ceiling effects (Lannin, 2004; Hsueh & Hsieh, 2002; Williams, Galea & Winter, 2001). As a result of previous research the general tonus item, designed to measure muscle tone, has been removed from the MAS due to low reliability (Aamodt, Kjendahl & Jahnsen, 2006; Loewen & Anderson, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by many researchers, the MAS has significant floor and ceiling effects (Lannin, 2004; Hsueh & Hsieh, 2002; Williams, Galea & Winter, 2001). As a result of previous research the general tonus item, designed to measure muscle tone, has been removed from the MAS due to low reliability (Aamodt, Kjendahl & Jahnsen, 2006; Loewen & Anderson, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the scales recommended for post-stroke patients 18 and it has great potential in clinical assessment and in post-stroke rehabilitation research 13,14,26,27 . In the present study, both intra-and interrater reliability of the Portuguese version of the MAS were evaluated, with the participation of 23 physical therapists and 15 post-stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MAS has been extensively used in research and clinical practice worldwide 12,15,26 , and it includes both qualitative and quantitative aspects of functional tasks 12,[14][15][16]26 . It is one of the scales recommended for post-stroke patients 18 and it has great potential in clinical assessment and in post-stroke rehabilitation research 13,14,26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,15] Subsequent Rasch analysis confirmed that for item eight, the motor behaviours are not ordered hierarchically. [9][10][11]16] Consistently, the two most difficult behaviours for stroke survivors to achieve on the advanced hand activities item are motor behaviours three and four. These two motor behaviours involve drawing 10 horizontal lines and making 10 dots in a set timeframe respectively and will hereafter be referred to as the 'lines task' and 'dots task'.…”
Section: Introductionmentioning
confidence: 96%